Yop Fusions to Tightly Folded Protein Domains and Their Effects on Yersinia enterocolitica Type III Secretion - Lee, Vincent T. (American Society for Microbiology, 2002)
Yersinia enterocolitica organisms secrete Yop proteins via the type III pathway. Translational fusion of yop genes to ubiquitin or dihydrofolate reductase results in hybrid proteins that cannot be secreted. The folding of hybrids prevents their own transport, but it does not hinder the type III secretion of other Yops.